2001
DOI: 10.2307/3803028
|View full text |Cite
|
Sign up to set email alerts
|

Declining Scaup Populations: A Retrospective Analysis of Long-Term Population and Harvest Survey Data

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
148
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 7 publications
3
148
3
Order By: Relevance
“…Diet data were included from 22 scaup collected in 2000-2001 at Thief Lake and Roseau River (Anteau and Afton 2006) for reference; those data were included into subsequent analyses as a separate region (Northwestern Minnesota 2000-2001). Samples were pooled over years and it was assumed that annual variation was less important than spatial variability Anteau and Afton 2006;Anteau and Afton 2008b).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…Diet data were included from 22 scaup collected in 2000-2001 at Thief Lake and Roseau River (Anteau and Afton 2006) for reference; those data were included into subsequent analyses as a separate region (Northwestern Minnesota 2000-2001). Samples were pooled over years and it was assumed that annual variation was less important than spatial variability Anteau and Afton 2006;Anteau and Afton 2008b).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The continental scaup population (Lesser [ Aythya affinis ] and Greater Scaup [ A. marila ] combined) has declined markedly since 1978 (Austin et al 1998;Afton and Anderson 2001); population estimates were lowest on record in 2006 (Wilkins et al 2007). Afton and Anderson (2001) concluded that the decline in the continental scaup population likely is driven by declines in the Lesser Scaup population and caused by reductions in recruitment.…”
mentioning
confidence: 99%
See 3 more Smart Citations